Pengaruh Low Organized Games terhadap Derajat Kebugaran Jasmani Siswa Sekolah Dasar - Hidayat, Rizki Aulia; Budiana, Dian; Situmorang, Andi Suntoda (TEGAR: Journal of Teaching Physical Education in Elementary School, 2020)
This study is motivated by learning low organized games as a support in improving physical fitness. This study aims to develop a low organized games learning program in physical education to improve students physical fitness. The method used in this study is an experiment with a pretest posttest control group design. The population in this study were fifth grade students. The sample in this study was 62 students This study was conducted as many as 12 meetings. Data processing using SPSS software version 22.00 for Windows. The results showed that there was a significant effect of the implementation of learning low organized games on the degree of physical fitness students, there was a significant effect of the application of control group learning on the physical fitness degree of students, and learning of low organized games was more influential compared to control group learning on physical fitness degrees of students.Â AbstrakStudi ini dilatarbelakangi pembelajaran low organized games sebagai penunjang dalam meningkatkan kebugaran jasmani. Studi ini bertujuan untuk mengembangkan program pembelajaran low organized games dalam pendidikan jasmani untuk meningkatkan kebugaran jasmani siswa. Metode yang digunakan dalam studi ini yaitu eksperimen dengan desain pretest posttest control group design. Populasi dalam studi ini yaitu siswa kelas V. Sampel dalam studi ini sebanyak 62 siswa. Studi ini dilakukan sebanyak 12 kali pertemuan. Analisis data yang dilakukan yaitu dengan bantuan software SPSS versi 22.00 for Windows. Hasil studi menunjukkan terdapat pengaruh yang signifikan dari penerapan pembelajaran low organized games terhadap derajat kebugaran jasmani siswa, terdapat pengaruh yang signifikan dari penerapan pembelajaran kelompok kontrol terhadap derajat kebugaran jasmani siswa, dan pembelajaran low organized games lebih berpengaruh dari pembelajaran kelompok kontrol terhadap derajat kebugaran jasmani siswa.